P164 Celiac Disease among a large cohort of inflammatory bowel disease patients: epidemiology and outcome implications. (27th May 2021) - Vernero, M; Ribaldone, D G; Giudici, G; Stalla, F M; Dutto, C; Bugianesi, E; Saracco, G M; Caviglia, G P; Astegiano, M
Abstract: Background: Inflammatory bowel disease (IBD), including Crohn's disease (CD), ulcerative colitis (UC) and undetermined IBD (IBD-U), are autoimmune chronic remittent diseases affecting the gut. On the other hand celiac disease (CeD) is a gluten related disorder leading to duodenal villous atrophy. Lately, the link between CeD and IBD has become of growing interest. Indeed, CeD prevalence among IBD population has been widely investigated, as well as IBD prevalence in CeD population. Particularly, IBD seems to have a significantly higher prevalence among CeD population than in general population and CeD seems to be more prevalent in IBD population. However, there is still lack of data on whether CeD can influence IBD outcome. So, primary outcome of our study is to measure prevalence of CeD among IBD population and secondary outcome is to evaluate possible influence of CeD on IBD outcome. Methods: Data were collected from march 2020 to September 2020 from IBD internal registry in San Giovanni Antica Sede Hospital in Turin. To detect CeD patients, all patients were screened and the ones with a reported duodenal lesion were selected. From those, the ones with defined diagnosis of CeD (presence of serum IgA antitransglutaminase and or IgA anti endomisial antibodies) were finally selected. Prevalence of CeD among IBD was compared to that of general population basing on literature. Then 76 patients were randomly selected as control group, in roder to investigate secondary outcome. To define IBD as complicated Siegel's score was used (1 out of five item needed to define complicated disease). Results: Among 5732 IBD patients we detected 80 patients with duodenal lesions, of whom 27 were diagnosed with CeD. So, prevalence of CeD among our population is about 0, 49% whiich is similar to that of general population (0, 48%, P=0.98). No differences were found in CeD prevalence among CD, UC and IBD-U subgroups. As regards secondary outcome, in case group complicated IBD was 44, 4% while among control group 26, 3% (p=0.08). In a mean follow up time of 133, 93 months, mean time from diagnosis to complication of IBD was 58, 2 months in case group and 102, 7 months in control group. As shown in figure 1, Kaplan-Maier curve for event free survival comparing the two groups shows a significant difference between CeD + IBD patients and IBD only patients (p=0, 002). Conclusion: Even though the retrospective nature of the study could lead to underestimate CeD diagnosis, among our cohort of IBD patients CeD prevalence seems not to be significantly higher than among general population. Despite of that, when associated to CeD, IBD seems to have earlier complications, so these patients may deserve a top down therapeutical approach and/ or a more strict follow up.